An overview of randomized controlled trials on endovascular treatment for chronic cerebrospinal venous insufficiency in multiple sclerosis patients - Simka, Marian (Phlebologie, 2020)
About ten years ago it was hoped that venous angioplasty for abnormal veins, primarily the internal jugular veins, will be a much awaited treatment for multiple sclerosis. Yet, a majority of randomized clinical trials on endovascular treatment for chronic cerebrospinal venous insufficiency did not reveal clinical efficacy of these procedures in multiple sclerosis patients. Still, a detailed analysis of these trials suggests that they were poorly designed, underpowered and endovascular techniques used were often far from being optimal. Nonetheless, even considering weak points of these trials, it can be concluded that venous angioplasty should not be used as a routine treatment modality in multiple sclerosis patients. Still, a possibility that some patients may benefit from endovascular treatment cannot be ruled out. This may concern patients at early stage of the disease and presenting with lesions that can easily be managed with balloon angioplasty. Therefore, we need more studies evaluating clinical efficacy of venous angioplasty in selected subgroups of multiple sclerosis patients. Importantly, it has already been demonstrated that venous angioplasty in multiple sclerosis patients is a safe procedure. Thus, also from an ethical point of view, such trials seem justifiable.
Keywords: chronic cerebrospinal venous insufficiency; internal jugular vein; multiple sclerosis; randomized clinical trial